Panic prescribing has become omnipresent during the COVID-19 pandemic - Caplan, Arthur L.; Upshur, Ross (The Journal of clinical investigation, 2020)
The President of the United States has repeatedly touted hydroxychlororquine as a likely cure for COVID-19 and urged Americans to try it, stating at one of his media briefings, "What do you have to lose? What do you have to lose? Take it" (1). A few others around the world have chimed in to promote one drug or another, this drug in combination with others, or their own favorite untested nostrums. This has led to drug hoarding, the inability of patients who actually need and benefit from certain drugs to access them, and serious side effects and even deaths from self-medication. As it was unclear at the time whether any benefit would come from these interventions, a mechanism called monitored emergency use of unregistered and investigational interventions (MEURI) was created as a bridge to clinical trials in order to curtail unconstrained use of medications.